Efficient Tandem Organic Light Emitting Diode Using Organic Photovoltaic Charge Generation Layer - Akanksha Jetly; Rajesh Mehra (International Journal of Optics)
Highly efficient tandem red OLED is proposed using planar organic heterojunction based charge generation layer (CGL) of C70 (Fullerene)/CoPc (Cobalt Phthalocyanine). The proposed charge generation layer generates charges and exhibits organic photovoltaic type (OPV) behavior in the red emitter zone which helps in slower efficiency roll-off at higher current densities. In addition an ultrathin layer of Al/LiF is used as electron injection layer (EIL) so as to enhance the injection of electrons from charge generation layer to emissive unit. It is found that the tandem red device can reach current efficiency and luminance of 26 cd/A and 26039 cd/m2 at 20 mA/cm2 and 100 mA/cm2, respectively, which is 1.663 times and 1.665 times higher than the corresponding single emitter device. Moreover, it is known that the tandem device requires double turn-on voltage than conventional devices. In this work, the turn-on voltage of red tandem device (5.85 V) is found to be less than twice the voltage of conventional device (3 V). Further with the introduction of Distributed Bragg Reflector (DBR), enhancement in current efficiency and brightness of tandem red device are observed due to high reflectance property of DBR. Thus, the effective charge generation and OPV function of proposed charge generation layer as well as remarkably high injection property of EIL layer lead to the high performance tandem OLED.